Eksplorasi Jukstaposisi Visual dalam Novel Grafis ‘The Photographer’ - Adya Arsita; Daru Tunggul Aji (Rekam : Jurnal Fotografi, Televisi, Animasi, 2020)
The Exploration of Visual Juxtaposition in a Graphic Novel titled ‘The Photographer’. Comic as a story book full of drawings is now popular under the name of graphic novel, which in its development begins to vary.  A graphic novel titled ‘The Photographer: Into War-Torn Afghanistan with Doctors without Borders’ presents two types of pictorial texts, which are drawings in comic styles and photographic works.  The study of this graphic novel aims to explore the visual juxtaposition of the comics and photographs by establishing the graphic novel as the narrative medium in delivering the message and context as well as how they intertwine with each other since there are two types of pictorial texts.  The development of technology in photography has made it possible to actuate photography juxtaposed with other visual media which have come to popularity in advance, to blend, and to combine a unique and specific narrative combination.  The method employed in this research is a qualitative method that believes in a holistic reality as a result of a construction of comprehension of case by case since the characteristic of each case is different one to another. Besides that, the multimodal discourse is also employed as an approach proportionally to evaluate the effectiveness of the message and the contextual meaning of its visual juxtaposition. Therefore, the result is expected to bridge over the understanding of various visual texts given sequentially by using the approach of multimodal discourse as the instrument for an effective communication in enhancing the visual literacy.  ABSTRAKKomik sebagai sebuah buku cerita bergambar yang kini lebih dikenal dengan istilah  novel grafis, makin hari makin berkembang keragamannya.  Dalam sebuah novel grafis yang berjudul The Photographer: Into War-Torn Afghanistan with  Doctors without Borders disajikan dua jenis teks piktorial, yaitu dalam gambar komik dan karya foto.  Pengkajian novel grafis ini akan mencoba mengeksplorasi jukstaposisi visual yang berupa gambar komik dan hasil karya fotografi dengan menempatkan novel grafis sebagai media naratif dalam menyampaikan pesan dan makna serta menilik saling keterkaitannya satu sama lain dengan munculnya dua ragam jenis teks piktorial.  Perkembangan teknologi dalam dunia fotografi membuat fotografi mampu menyandingkan diri dengan media visual lain yang lebih dahulu populer, melebur dengan saksama, dan menciptakan kombinasi naratif yang unik dan spesifik. Metode yang dipakai dalam penelitian ini adalah metode kualitatif dengan prinsip bahwa suatu realitas yang bersifat menyeluruh adalah sebagai hasil konstruksi dari pemahaman terhadap kasus per kasus karena sifat suatu masalah yang satu berbeda dari yang lain.  Selain itu, pendekatan kajian dengan multimodal discourse juga akan diaplikasikan untuk meninjau efektivitas pesan dan pemaknaan jukstaposisi visualnya. Dengan demikian, hasil analisis diharapkan akan membantu menjembatani  pemahaman teks visual yang hadir secara beragam secara sekuensial dengan pendekatan wacana multimodal sebagai upaya komunikasi yang efektif dalam meningkatkan literasi visual.